Semiclassical approach for solving the time-dependent Schr\"odinger equation in spatially inhomogeneous electromagnetic pulses - Li, Jianxiong; Thumm, Uwe (My University, 2020)
To solve the time-dependent Schrödinger equation in spatially inhomogeneous pulses of electromagnetic radiation, we propose an iterative semiclassical complex trajectory approach. In numerical applications, we validate this method against ab initio numerical solutions by scrutinizing (a) electronic states in combined Coulomb and spatially homogeneous laser fields and (b) streaked photoemission from hydrogen atoms and plasmonic gold nanospheres. In comparison with streaked photoemission calculations performed in strong-field approximation, we demonstrate the improved reconstruction of the spatially inhomogeneous induced plasmonic infrared field near a nanoparticle surface from streaked photoemission spectra.